LEGAL REVIEW OF PARATE EXECUTIE OF MORTGAGE RIGHTS IN PROTECTING THE RIGHTS OF SEPARATE CREDITORS IN BANKRUPTCY PROCEEDINGS - Lestari, Insan Indah; Waluyo, Waluyo (SYNTIFIC, 2024)
Background. The existence of collateral in bank credit agreements is crucial as one of the legal safeguards for the bank's security in mitigating risks. This is to ensure that the debtor will repay the loan. Even though the debtor might go bankrupt, creditors who have secured their loans with mortgages or other similar agreements have special rights. These rights protect them in case the debtor can't pay back the loan. Research Methods. This research investigates the parate executie regulations under Indonesian bankruptcy law and examines the legal protection available to separate creditors in the presence of parate executie. A normative juridical research method was used, with data collected through a literature and document review. Findings. The results of the study show that the bankruptcy case of a limited liability company causes creditors to lose their civil rights to control and manage the assets of an individual who has been included in the bankrupt estate, where separate creditors have a separate position to be prioritized in the repayment of their claims. Conclusion. The crux of the matter lies in the discord between bankruptcy and mortgage laws. While bankruptcy law imposes a moratorium on creditor enforcement actions, mortgage law accords creditors a more immediate right of execution. This legal dissonance creates uncertainty for secured creditors like PT. BM. To rectify this situation, a reconciliation of these two legal frameworks is essential.